[Papers relating to the affairs of the Hudson's Bay Company, sales of land, trade policy, etc.] [electronic resource]. - Rose, John, Sir, 1820-1888.; Hudson's Bay Company. ([London? : s.n., 1882)
Caption title: Letters from Sir John Rose to the Governor. Electronic reproduction. Mode of access: Internet. 44